Wybrane problemy rozwoju demograficznego i społecznego Bydgoszczy w latach siedemdziesiątych XX wieku (Kronika Bydgoska, 2012)
The article is an attempt at describing the city and its residents from the angle of statistical data conceming natural movement, households and their residents. The first part of the work presents an analysis of the population, migrations, new marriages, live births, demises and divorces, and the second part - the number of families and family stmcture, the number of offspring, sources of maintenance, education reąuirements, etc. The author describes also selected social processes accompanying the rapid industrialisation in the period of the govemment of Edward Gierek (family disintegration, high infant and baby mortality ratę, increase in mortality ratę, and permanent crisis haunting health education in the city). The analysis includes several statistical tabular registers.